PERBANDINGAN KEMAMPUAN CALISTUNG SISWA KELAS II SDN 79 PEKANBARU DENGAN PENERAPAN PENDEKATAN TEMATIK SAINTIFIK - Ulil Meisal, dkk (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2014)
The research method used is a quasi-experimental method which consists of experimental class and class II controlkelas SDN 79 Pekanbaru, which illustrates a significant difference in the ability to calistung between the two. Research on the data pretest seen from arithmetic average of the experimental 70.66 and control 65.9, experimental writing skills 77, and controls 71.6, experimental ability to read 76, and controls 77.5. To find significant differences in the ability of the chi square analysis was used to calculate the ability Xhitung <Xtabel (1.67 <3.841), there was no significant difference, the ability to write with Xhitung <Xtabel (0.6 <3.841), there was no significant difference on writing skills, and the ability to read with Xhitung <Xtabel (1.12 <3.841), there was no significant difference in reading ability. Posttest data seen from the average value of the experimental class numeracy 75.6 and 71.7 control, the ability to write an experimental class 81.9 and control 74.6, literacy class experimental 82.1 and control 78.5. To determine differences in the ability to use the chi square analysis on numeracy Xhitung <Xtabel (3.51 <3.841), there was no significant difference in the experimental class and the control class numeracy skills. The ability to write with Xhitung <Xtabel (3.51 <3.841), there was no significant difference, while the ability to read Xhitung <Xtabel (0.71<3.841), there was no significant difference. Improved results in the experimental class capabilities calistung numeracy skills of 0.15, and control 0.16, the ability to write of 0.26, and control 0.11, the ability to read the experimental class of 0.31, and controls 0.07, it is seen larger in capacity building calistung the experimental class.